Physiological Ecology of Microorganisms in Subglacial Lake Whillans - Vick-Majors, Trista J.; Mitchell, Andrew C.; Achberger, Amanda M.; Christner, Brent C.; Dore, John E.; Michaud, Alexander B.; Mikucki, Jill A.; Purcell, Alicia M.; Skidmore, Mark L.; Priscu, John C.; , The WISSARD Science Team (Frontiers in Microbiology, 2016)
Subglacial microbial habitats are widespread in glaciated regions of our planet. Some of these environments have been isolated from the atmosphere and from sunlight for many thousands of years. Consequently, ecosystem processes must rely on energy gained from the oxidation of inorganic substrates or detrital organic matter. Subglacial Lake Whillans (SLW) is one of more than 400 subglacial lakes known to exist under the Antarctic ice sheet; however, little is known about microbial physiology and energetics in these systems. When it was sampled through its 800 m thick ice cover in 2013, the SLW water column was shallow (~2 m deep), oxygenated, and possessed sufficient concentrations of C, N, and P substrates to support microbial growth. Here, we use a combination of physiological assays and models to assess the energetics of microbial life in SLW. In general, SLW microorganisms grew slowly in this energy-limited environment. Heterotrophic cellular carbon turnover times, calculated from 3H-thymidine and 3H-leucine incorporation rates, were long (60 to 500 days) while cellular doubling times averaged 196 days. Inferred growth rates (average ~0.006 d-1) obtained from the same incubations were at least an order of magnitude lower than those measured in Antarctic surface lakes and oligotrophic areas of the ocean. Low growth efficiency (8%) indicated that heterotrophic populations in SLW partition a majority of their carbon demand to cellular maintenance rather than growth. Chemoautotrophic CO2-fixation exceeded heterotrophic organic C-demand by a factor of ~1.5. Aerobic respiratory activity associated with heterotrophic and chemoautotrophic metabolism surpassed the estimated supply of oxygen to SLW, implying that microbial activity could deplete the oxygenated waters, resulting in anoxia. We used thermodynamic calculations to examine the biogeochemical and energetic consequences of environmentally imposed switching between aerobic and anaerobic metabolisms in the SLW water column. Heterotrophic metabolisms utilizing acetate and formate as electron donors yielded less energy than chemolithotrophic metabolisms when calculated in terms of energy density, which supports experimental results that showed chemoautotrophic activity in excess of heterotrophic activity. The microbial communities of subglacial lake ecosystems provide important natural laboratories to study the physiological and biogeochemical behavior of microorganisms inhabiting cold, dark environments.